Removal Color Study of Toluidine Blue dye from Aqueous Solution by using Photo-Fenton Oxidation - Baghdad Science Journal (مجلة بغداد للعلوم)
The degradation of Toluidine Blue dye in aqueous solution under UV irradiation is investigated by using photo-Fenton oxidation (UV/H2O2/Fe+). The effect of initial dye concentration, initial ferrous ion concentration, pH, initial hydrogen peroxide dosage, and irradiation time are studied. It is found put that the removal rate increases as the initial concentration of H2O2 and ferrous ion increase to optimum value ,where in we get more than 99% removal efficiency of dye at pH = 4 when the [H2O2] = 500mg / L, [Fe + 2 = 150mg / L]. Complete degradation was achieved in the relatively short time of 75 minutes. Faster decolonization is achieved at low pH, with the optimal value at pH 4 .The concentrations of degradation dye are detected by spectrophotometer at ?max =626 nm. The order of photo degradation reaction under UV is the first order kinetics. The photo-Fenton degradation process was monitored by UV-visible spectrophotometer.